Status Data and Communication Aspects in Dynamically Clustered Network-on-Chip Monitoring. (16th February 2012) - Rantala, Ville; Liljeberg, Pasi; Plosila, Juha
Abstract : Monitoring and diagnostic systems are required in modern Network-on-Chip implementations to assure high performance and reliability. A dynamically clustered NoC monitoring structure for traffic and fault monitoring is presented. It is a distributed monitoring approach which does not require any centralized control. Essential issues concerning status data diffusion, processing, and format are simulated and analyzed. The monitor communication and placement are also discussed. The results show that the presented monitoring structure can be used to improve the performance of an NoC. Even a small adjustment of parameters, for example, considering monitoring data format or monitoring placing, can have significant influence to the overall performance of the NoC. The analysis shows that the monitoring system should be carefully designed in terms of data diffusion and routing and monitoring algorithms to obtain the potential performance improvement.